GE_GERICHTE P/15431/2012 vom 30. Mai 2014 - GE Cour de justice (2014)
PREUVE; VOL(DROIT PÉNAL); PAR MÉTIER; LIBÉRATION CONDITIONNELLE; RÉCIDIVE(INFRACTION); FIXATION DE LA PEINE; CONCOURS D'INFRACTIONS | CP.139.2; CP.47; CP.49.1; CP.49.2; CP.46.1; CP.46.2; CP.89